Gender, Political and Economic Instability, and Trafficking into Forced Marriage - Kakar, Muhammad Makki (Women & criminal justice, 2022)
This article showcases the lived experiences of Afghan women and girls trafficked into forced marriage in Balochistan province of Pakistan and identifies the processes that lead to their exploitation. Situating forced marriage within the ambit of human trafficking, the study highlights the gendered/aged/classed aspects of the phenomenon and unveils how it is linked to other forms of trafficking. Women and girls trafficked into forced marriage experience multiple forms of exploitation, stigmatization, and social isolation throughout their lives. The study pinpoints that this form of trafficking generally remains outside the radar of anti-trafficking policies which further enhance the vulnerabilities of trafficked victims.